Quality Assessment of the Physico-Mechanical and Elemental Composition of Three Pencil Grades and Eraser Types Produced in Nigeria - K. I. Omoniyi; P. A. Ekwumemgbo; J. Emmanuel (Nigerian Journal of Technological Development, 2014)
The quality assessment of the physical (pH, electrical conductivity, density, writeability, eraseability), mechanical (compression test and break strength) and elemental composition of the pencil grades HB, 2B and 3B and eraser types of brand names Ben 10, Tiky 20 and the commonest White eraser in Nigerian primary school (Gummes Co. China) was carried out. The diameter of the graphite part increased in the order HB < 3B < 2B. The pH range of the pencil types was 7.0 – 7.4. 2B pencil exhibited the best writeability quality followed by 3B pencil. The compression qualities of the three pencil types were not statistically different (P < 0.01). 3B pencil is the strongest of the pencil types studied, while HB has the least break strength. Cr level by atomic absorption spectrophotometry was lowest in 3B pencil (1.541 μg/g) and highest in 2B (3.700 μg/g). Level of Pb was higher in 2B and HB (4.688 μg/g), while Cd was highest in HB (1.633 μg/g). Fast neutron activation technique indicated that Fe and Zn were elevated compared to the levels of Cr, Cd and Pb in the pencils. The pH range of the eraser brands was 6.2 – 7.3. The best eraseability quality was in Tiky 20 and the worst in Ben 10 eraser. The eraser brands contain some heavy metals in the order Pb > Cr > Cd. Though, the levels of the trace metals and essential elements detected in the school items are below the recommended limits, regulatory measures should be directed towards maintaining the standards of school items.